2012
DOI: 10.3102/0002831211427206
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study of School-Linked, Collective Parent Engagement

Abstract: This article explores the social processes and outcomes associated with a school-linked, community-based program that successfully engages Latino parents and children in a low-income school community. Framed by an ethnographic, embedded case study design, the authors collected data from 32 Latino parents. The findings detail parents' experiences when first entering the neighborhood and how these experiences shape their engagement with other parents in the program and neighborhood community. We conclude that ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 46 publications
0
56
0
Order By: Relevance
“…This collaborative is developed to enhance family access to, and use of, school-community services and resources. When effectively implemented, past versions of these collaboratives have facilitated significant shifts/improvements in the design and delivery of schoolcommunity services (Alameda- Lawson & Alameda-Lawson, 2012). One example of this shift is the transfer of professional roles from solo service providers to a more flexible, bottom-up approach that builds on family and community strengths.…”
Section: Collective Parental Engagementmentioning
confidence: 99%
See 1 more Smart Citation
“…This collaborative is developed to enhance family access to, and use of, school-community services and resources. When effectively implemented, past versions of these collaboratives have facilitated significant shifts/improvements in the design and delivery of schoolcommunity services (Alameda- Lawson & Alameda-Lawson, 2012). One example of this shift is the transfer of professional roles from solo service providers to a more flexible, bottom-up approach that builds on family and community strengths.…”
Section: Collective Parental Engagementmentioning
confidence: 99%
“…As such, CPE efforts are typically designed to develop and mobilize social networks that can help parents address institutional-level problems that cannot be easily understood or changed by individuals working in isolation from one another (Ishimaru, Barajas-López, & Bang, 2015;Lawson & Alameda-Lawson, 2012).…”
Section: Collective Parental Engagementmentioning
confidence: 99%
“…Research has shown that engaging schools, parents, and communities in partnership improves children's educational outcomes (Lamb-Parker et al, 2001;Lawson & Alameda-Lawson, 2012). Moreover, parental engagement has been theoretically linked to improved student behavior and academic achievement in schools (Hill & Taylor, 2004;Kingston et al, 2013).…”
Section: Parent Engagement As a Determinant Of Educational Successmentioning
confidence: 99%
“…Michael Lawson and Tania Alameda-Lawson (2011) also find that social networks and parent associations can reduce students' problems. For example, it is important that parents take part when their children are doing homework.…”
Section: Abstrakmentioning
confidence: 99%